Congenital pseudarthrosis of the proximal tibia: a case report - Weng, Jiewei; Wang, Jiaqi; Li, Tianyou (Frontiers in Pediatrics, 2026)
Congenital pseudarthrosis of the tibia (CPT) is a rare and challenging pediatric orthopedic disorder that predominantly affects the distal or middle third of the tibia, with involvement of the proximal third being exceedingly rare. Literature on this condition remains limited. This case presents proximal tibial CPT with proximal tibial dysplasia in a 7-year-old male patient with neurofibromatosis type 1. Based on the fundamental treatment principles of CPT, the child underwent pseudarthrosis resection, bone grafting, and internal fixation with a Rush rod combined with a plate. Following the achievement of initial successful union, hemiepiphysiodesis was employed to correct the genu valgus deformity. This case report proposes a hypothesis regarding the formation mechanism of proximal tibial CPT and provides clinical support for the standardized diagnosis and management of CPT.